Analysis of Madm, a novel adaptor protein that associates with Myeloid Leukemia Factor 1 - Lim, Raelene (Curtin University, 2003)
Myeloid Leukemia Factor 1 (Mlf1) is the murine homolog of MLF1, which was identified as a fusion gene with Nucleophosmin (NPM) resulting from the (3;5)(q25.1;q34) translocation associated with acute myeloid leukemia and myelodysplastic syndrome (Yoneda-Kato et al., 1996). Mlf1 was independently isolated using cDNA representational difference to identify genes up-regulated when an erythroleukemic cell line underwent a lineage switch to display a monoblastoid phenotype (Williams et al., 1999). Mlf1 has been shown to enhance myeloid differentiation and suppress erythroid differentiation; however, its mechanism of action is unknown. A yeast two hybrid screen was employed to identify Mlf1-interacting proteins. This screen isolated a number of known protein, as well as several novel molecules, that bound Mlf1. One of these was 14-3-3ξ, a member of a family of molecules that bind phosphoserine motifs and regulate the subcellular localization of partner proteins. Mlf1 contains a classic RSXSXP sequence for 14-3-3 binding and associated with 14-3-3ξ; via this phosphorylated motif (Lim et al., 2002). The aim of this thesis was to characterise a novel Mlf1-interacting protein that had some homology to protein kinases and was named Mlf1 Adaptor Molecule (Madm). Adaptor proteins are molecules that possess no enzymatic or transcriptional activity, but instead mediate protein-protein interactions. Madm is encoded by a gene consisting of 18 exons and promoter analysis suggested Madm expression might be widespread; indeed Northern blotting of adult tissues and in situ hybridization of embryos demonstrated ubiquitous Madm expression. Significantly, the Madm protein sequence is highly conserved across diverse species.Madm formed dimers and although it contains a kinase-like domain, the protein lacks several critical residues required for catalytic activity, including an ATP-binding site. Purification of recombinant Madm revealed that the protein was not a kinase; however, studies in mammalian cells showed that Madm associated with a kinase and that Madm was phosphorylated on serine residues in vivo and in vitro. Madm also contains a nuclear localization sequence and nuclear export sequence and was shown to localise to both cytoplasm and nucleus by subcellular fractionation and confocal microscopy. The presence of two nuclear receptor binding motifs (consensus MILL) suggests that Madm may have a functional role in the nucleus. Madm co-immunoprecipitated with Mlf1 and co-localized in the cytoplasm. In addition, the Madm-associated kinase phosphorylated Mlf1 on serine residues, including the RSXSXP motif. In contrast to wild-type Mlf1, the oncogenic fusion protein NPM-MLF1 did not bind 14-3-3i; and localized exclusively in the nucleus. Although Madm co-immunoprecipitated with NPM-MLF1 the binding mechanism was altered. As Mlf1 is able to reprogram erythroleukemic cells to display a monoblastoid phenotype and potentiate myeloid maturation (Williams et al., 1999), the effects of Madm on myeloid differentiation was investigated. However, unlike Mlf1, ectopic expression of Madm in M1 myeloid cells suppressed cytokine-induced differentiation.In summary, the data presented in this thesis reports on the cloning and characterization of a novel adaptor protein that is involved in the phosphorylation of the proto-oncoprotein MIM. Phosphorylation of Mlf1 is likely to affect its interaction with other proteins, such as 14-3-3~. Complex formation, therefore, may well alter the localization of Mlf1 and Madm, and influence hematopoietic differentiation.